Long-term/home parenteral nutrition: expert consensus statements regarding intravenous lipid emulsions - Mundi, Manpreet S.; Martindale, Robert G.; Calder, Philip C.; Klek, Stanislaw (Frontiers in Nutrition, 2025)
Home parenteral nutrition (HPN) is the primary life-saving therapy for patients with chronic intestinal failure (CIF). Patients requiring palliative nutrition, such as those with advanced cancer, may also benefit from HPN. Lipids are an integral part of parenteral nutrition (PN), but the use of intravenous lipid emulsions (ILEs) in PN continues to raise numerous questions for clinicians despite improved understanding and knowledge. The Lipids in PN Summit involved a panel of international experts with extensive research and clinical experience in use of PN. They assessed the current state of knowledge and developed expert consensus statements regarding the use of ILEs in patients requiring PN. The statements are also provided to help bridge the gaps between evidence and clinical practice, hence complementing formal societal guideline recommendations for the use of PN. This review briefly summarizes the rationale for considering ILE choice as a central component of any strategy for HPN patients, and discusses aspects of special interest within the context of HPN and long-term PN use in general such as essential fatty acid (EFA) delivery, the prevention of IF-associated liver disease (IFALD), and clinical evidence within HPN populations. In particular, potential clinical advantages of modern composite ILEs containing fish oil are reviewed, with biological effects of omega-3 polyunsaturated fatty acids (PUFAs) imparting additional clinical benefits. A future perspective section shares some proposals to address the difficulties of data generation within HPN, and suggested approaches to take as part of current clinical practice in the absence of definitive data. For now, the existing body of evidence should provide the basis for clinical care, and where evidence is lacking expert recommendations must suffice. The consensus statements from the Lipid Summit aim to summarize aspects mostly relevant for everyday clinical care; those relevant to the HPN setting are presented in this review.